The Role of Key Opinion Leaders and Customer Experience on Purchase Decisions: The Mediating Effect of Brand Image - Prasetyo Hartanto; Lawrence Adi Supriyono; Antonius Juniarto (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
Background: Indonesia has become one of the countries with the highest number of mobile game downloads, with a total of 3.65 billion downloads in 2023, emerging as one of the largest mobile game markets in the world. This study examines the role of Key Opinion Leaders and Customer Experience in purchasing decisions for hero skins in the Mobile Legends game, with Brand image as a mediating variable. This study aims to understand the relationship between variables and their impact on consumer behavior. Research method: The type of research used in this study is quantitative exploratory. Exploratory research is a type of research that examines the causal relationship between the variables used in this study. The population used in this study are consumers who have purchased Mobile Legends skins within the past year. The sample size in this study is 253 respondents. Research results: The descriptive analysis results for each indicator in the Key Opinion Leader, Customer Experience, Brand Image, and Purchase Decision variables are valid and reliable. The hypothesis in this study is accepted and has a high enough influence and significance. Conclusion: Based on the results of this study, it was found that Key Opinion Leaders and Customer Experience have a positive influence, both directly and indirectly, on Purchase Decision through Brand Image. These findings indicate that an approach that combines digital strategies through KOL and improved Customer Experience can strengthen Brand Image and encourage consumer purchasing decisions. This reinforces the important role of digital marketing communication and customer experience in the context of the creative and digital industries.